Associations among frailty status, hypertension, and fall risk in community-dwelling older adults - Liping Teng; Danhui Wang; Zhou Zhou; Jun Sun; Min Zhu; Renrong Wang (Elsevier, 2024)
Objectives: Frailty and hypertension often coexist in older adults, which may lead to fall risks. This study aimed to examine the relationship between frailty status, hypertension, and fall risk. Methods: In this cross-sectional study, a total of 401 older adults were conveniently recruited from communities in Wuxi, China, between September 2022 and November 2022. The fall risk self-assessment checklist from the Stopping Elderly Accidents, Deaths & Injuries (STEADI) Toolkit was used to evaluate their fall risks. The FRAIL scale questionnaire was used to assess frailty status. Participants' demographic information and comorbidities were collected. Multivariate logistic regression, generalized additive model, and smooth curve fitting were used to analyze the association between frailty, hypertension, and fall risk. Results: Frailty had a strong association with increased prevalence of fall risk among the participants (OR 8.52, 95% CI 3.21-22.57; P < 0.001). Hypertension significantly increased the fall risk among older adults (OR 1.87, 95% CI 1.11-3.13; P = 0.019). The group with hypertension and frailty had the highest prevalence of fall risk (OR 12.24, 95% CI 3.51-42.65). Smooth curve fitting showed a nonlinear association between frailty and fall risk in hypertension status. In the progress of pre-frailty to frailty status, a higher tendency to fall was found among older adults with hypertension. Conclusions: Frailty status and hypertension independently and jointly influenced the increased prevalence of fall risk. Enhanced frailty and hypertension management may help decrease fall risk among this population.